Knowledge, attitude and practice of sawmill workers towards noise-induced hearing loss in Kota Bharu, Kelantan - Mohd Rus, Razman; Daud, Aziah; Musa, Kamarul Imran; naing, Lin (Malaysian Journal of Medical Sciences, 2008)

(untitled)
The purpose of this study was to determine the sawmill workers’ knowledge, attitude and practice (KAP) in relation to noise-induced hearing loss (NIHL). A cross-sectional study was conducted involving 83 workers from 3 factories in Kota Bharu, Kelantan. Questionnaires were distributed to obtain the socio-demography, knowledge, attitude and practice level in relation to noise-induced hearing loss (NIHL). The weak areas identified in the knowledge section were treatment aspects (15.5%), signs and symptoms of NIHL (20.2%) and risk factors (31%). As for attitude; the prevention aspects were the lowest (25.3%), followed by risk taking attitude (26.2%), and causes of hearing loss (42.1%). Overall, the practice was not encouraging at all. It is important to have an education program to raise workers’ awareness and to improve their attitude and practices towards noise-induced hearing loss.